El tratamiento de los personajes femeninos en algunas novelas gráficas contemporáneas sobre la Guerra Civil española - Francesca Crippa (Cahiers de Civilisation Espagnole Contemporaine)
In the last few decades, many authors of graphic novels have been deciding to represent the Spanish civil war as the main theme within their works. At the same time, they have also been trying to emphasize the necessity of bringing back the memory of those categories who suffered its cruelest consequences. In the representation of women characters, particularly, the contemporary authors use very different strategies. The aim of this work is to analyze them in order to rethink the importance of the role played by women during the years of the Spanish civil war.